2022
DOI: 10.1111/andr.13143
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of gut microbiome in male reproduction

Abstract: Background The impact of the gut microbiome on the organism has become a growing research focus with the development of 16S rRNA sequencing. However, the effect of the gut microbiome in male reproduction has yet to be investigated. Objective To overview on possible mechanisms by which the gut microbiome could affect male reproduction and therapeutic opportunities related to the gut microbiome Methods Authors searched PubMed/MEDLINE, EMBASE, Web of Science, and Cochrane Library for medical subject headings term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 94 publications
0
36
0
Order By: Relevance
“…Bacterial translocation induced by abnormal intestinal permeability leads to oxidative stress, activates testicular LPS/TLR4, and transfers NF-κB and 10.3389/fmicb.2022.977574 mitogen-activated protein kinase to the nucleus through the MyD88 and TRAM pathways. This activates the innate immunity damaging testicular endothelium and the BTB (Wang and Xie, 2022).…”
Section: Gut Microbiota and Blood-testis Barriermentioning
confidence: 99%
“…Bacterial translocation induced by abnormal intestinal permeability leads to oxidative stress, activates testicular LPS/TLR4, and transfers NF-κB and 10.3389/fmicb.2022.977574 mitogen-activated protein kinase to the nucleus through the MyD88 and TRAM pathways. This activates the innate immunity damaging testicular endothelium and the BTB (Wang and Xie, 2022).…”
Section: Gut Microbiota and Blood-testis Barriermentioning
confidence: 99%
“…It has been suggested that a defective gut barrier function can end with the dissemination within the blood flow of microbial-associated molecular patterns (MAMPs) such as lipopolysaccharide, lipoprotein acids, peptidoglycans, and lipoproteins into the testis and epididymis. Indeed, immune system activation, induced by GM translocation, leads to testicular and epididymal inflammation and, also, triggers insulin resistance together with gastrointestinal hormones which, in turn, affect the secretion of sex hormones [luteinizing hormone (LH), follicle-stimulating hormone (FSH), and testosterone (T)] and their role in the regulation of spermatogenesis [ 89 ].…”
Section: Gut Microbiota and (In)fertilitymentioning
confidence: 99%
“…This condition determines: (i) the activation of specialized receptors known as pattern recognition receptors which serve as MAMP sensors that recognize the essential microbial components and trigger an immune response; (ii) Langerhans islet inflammation; and (iii) gastrointestinal hormonal changes with insulin resistance and the alteration of LH, FSH, and free T levels [ 89 ].…”
Section: Gut Microbiota and (In)fertilitymentioning
confidence: 99%
“…[13][14][15][16] Male susceptibility to cardiometabolic disorders earlier in life makes adopting and implementing steps to optimise the gut microbiome important. Moreover, the impact the gut microbiome appears to have on male fertility and testosterone availability 17 may be a factor in the considerable decrease in male fertility in the past 50 years.…”
Section: Enhancing the Microbiomementioning
confidence: 99%